Inclusion of PMU current phasor measurements in a power system state estimator - Chakrabarti, S.; Kyriakides, E.; Ledwich, G.; Ghosh, Arindam (The Institution of Engineering and Technology, 2010)
Three different methods of inclusion of current measurements by phasor measurement units (PMUs) ina power system state estimator is investigated. A comprehensive formulation of the hybrid state estimator incorporating conventional, as well as PMU measurements, is presented for each of the three methods. The behaviour of the elements because of the current measurements in the measurement Jacobian matrix is examined for any possible ill-conditioning of the state estimator gain matrix. The performances of the state estimators are compared in terms of the convergence properties and the variance in the estimated states. The IEEE 14-bus and IEEE 300-bus systems are used as test beds for the study.